Program Baitul Qiradh Dalam Pemberdayaan Ponorogo Makmur Perspektif Fiqih Muamalah ( Studi Kasus Baznas Ponorogo) Tahun 2022 - Aisi, Okta (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2022)
The Ponorogo Prosperous Baitul Qiradh Program of Baznas Ponorogo provides the needs needed by the community in economic activities, especially in mustahiq micro, small and medium enterprises, productive and innovative empowerment includes business capital assistance and business capital development to assist business partners and be able to manage until prosperity is achieved. With micro-business actors who become partners with Baznas, there will be no hassle in matters of business capital, because what is empowered is in the form of non-profit and is carried out independently of sharia.